"I Struggled But I Made It": Black Gifted Underachievers on Transitioning to College. Issue 2 (May 2020) - Sewell, Christopher J. P.; Goings, Ramon B.
Research on Black student presence in gifted and talented programs consistently illuminates issues with recruitment and underrepresentation. While enrolled, gifted Black students face a series of issues that affect their ability to persist and achieve, especially in nondiverse environments. This work examines the reflections of four Black adults who attended gifted schools in New York City and encountered significant hurdles during their K–12 schooling. These findings are excerpted from a larger qualitative study that investigated how Black adults, who were identified as gifted in New York City Public Schools, reflected on their experiences as gifted students and how they leveraged those experiences to persist to and through college. Using Schlossberg's model for adapting to transitions as the theoretical frame, findings suggest that participants received limited guidance as they transitioned to college but learned many lessons that led to become productive in college.